Correction: Impact of self-reported symptoms of allergic rhinitis and asthma on sleep disordered breathing and sleep disturbances in the elderly with polysomnography study. - Sae-Hoon Kim (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0173075.].